Child marriage in Malaysia: Whose rights are being Violated? / Noraine Bahari, Yarina Ahmad and Nor Azira Ayob - Bahari, Noraine; Ahmad, Yarina; Ayob, Nor Azira (2021)
Globally, the United Nations Children’s Fund (UNICEF) in 2006 revealed child marriage cases will significantly increase by 71% by the year 2030. A few years ago, the news of an 11-year-old girl married to a 41-year-old man at Gua Musang, Kelantan made headlines in Malaysian media. This news had shocked the nation as child marriage is an issue that requires careful discussion. Parents that agree on arranging child marriage for their child is primarily to avoid social stigma and believe that marriage is the best solution to solve social problems. This study uses a literature review. This paper will analyse and provide insights on child rights and the factors that led to child marriage. This paper reveals that child marriage is seen as a solution to social problems such as pre-marital sex out of wedlock pregnancy, and poverty. Nonetheless, this contradicted with the principle of prevailing the best interests of the child. Briefly, child marriage is a human right violation that takes away the childhood of a child. Thus, respective government agencies and communities need to take action to ensure that children specifically are being protected.